Integrative epigenetic taxonomy of primary prostate cancer. Issue 1 (December 2018) - Stelloo, Suzan; Nevedomskaya, Ekaterina; Kim, Yongsoo; Schuurman, Karianne; Valle-Encinas, Eider; Lobo, João; Krijgsman, Oscar; Peeper, Daniel; Chang, Seiwon; Feng, Felix; Wessels, Lodewyk; Henrique, Rui; et al.
Abstract The Androgen Receptor (AR) is the key-driving transcription factor in prostate cancer, tightly controlled by epigenetic regulation. To date, most epigenetic profiling has been performed in cell lines or limited tissue samples. Here, to comprehensively study the epigenetic landscape, we perform RNA-seq with ChIP-seq for AR and histone modification marks (H3K27ac, H3K4me3, H3K27me3) in 100 primary prostate carcinomas. Integrative molecular subtyping of the five data streams revealed three major subtypes of which two were clearly TMPRSS2-ERG dictated. Importantly, we identify a third subtype with low chromatin binding and activity of AR, but with high activity of FGF and WNT signaling. While positive for neuroendocrine-hallmark genes, these tumors were copy number-neutral with low mutational burden, significantly depleted for genes characteristic of poor-outcome associated luminal B-subtype. We present a unique resource on transcriptional and epigenetic control in prostate cancer, revealing tight control of gene regulation differentially dictated by AR over three subtypes. The Androgen Receptor (AR) is the main driver of prostate cancer and functions in conjunction with chromatin modifications. Here, the authors comprehensively profile 100 primary prostate carcinomas by sequencing RNA transcripts in combination with ChIP-sequencing for AR and the active histone marks H3K27ac, H3K4me3 and repressive mark H3K27me3.